'n Intertekstuele studie : Die werfbobbejaan van Alexander Strachan - Loots, Sonja (Rhodes University, Faculty of Humanities, School of Languages, 1998)
The title, "'n Intertekstuele studie: Die werfbobbejaan van Alexander Strachan", refers to an analysis of the way in which intertextual processes generate meaning in this text. It is analysed with specific regard to the way in which it enters into signifying and detennining relationships with other texts, notably texts by the same author. A significant part of the intertexts that are reassembled, refined, restated, amplified, contradicted or diffused throughout Die werfbobbejaan are located in other works in the Strachan oeuvre: n Wereld sonder grense (1984) and Die jakkalsjagter (1990). These three texts are related as a triptych of intertextual association, and the boundaries between them are not hermetically sealed. Intertextual activity in Die werfbobbejaan involves an intricate network of interfigural relationships. The identities of numerous characters in the text start to coincide with those of other characters to which they are linked intertextually. Characters travel across the boundaries supposedly separating "different" texts. The doubling and displacing of characters alert us to the fact that the text is not fixed within stable boundaries. Codes, scenes, snippets of dialogue and even moods also penetrate the boundaries between "different" texts and recur in the form of mirror images or ghostly transformations of themselves. These intertextual patterns mobilise an active reading process and unify the act of reading with that of writing in "a single signifying process" (Barthes 1979: 79). The narrator in Die werfbobbejaan is a woman writing a biography about an author. Reading his novels and unpublished manuscript she finds that the manuscript of her subject anticipates and later even dictates "extra-textual" reality and inserts her into the fiction. The way in which the biography is taken up in the play of intertextuality leads to the perception that the fictional author is an intertextual mirror image of the real author, who belongs to the extra-textual world outside the book. In this way intertextual activity in Die werfbobbejaan destabilizes the frame between fiction and reality. No reading of Die werfbobbejaan can be complete without taking into account the plurality of simultaneously perceived meanings triggered by intertextual activity in the text.
Keywords: Strachan, Alexander; Die Werfbobbejaan